Circuit analysis I : with MATLAB applications - Karris, Steven T. (Orchard Publications, 2004)
This text is an introduction to the basic principles of electrical engineering. It is intended for all engineering majors and presumes knowledge of first year differential and integral calculus and physics. The last two chapters include step-by-step procedures for the solutions of simple differential equations used in the derivation of the natural and forces responses. Appendix A is an introduction to MATLAB, and Appendices B and C provide a thorough review of complex numbers and matrices respectively.